Kajian pendahuluan penentuan tingkat utilitas pekerja proses filling stasiun kerja cup filling di perusahaan air minum dalam kemasan - Yanto, Yanto; Wahju, Marsellinus Bachtiar (Metris: Jurnal Sains dan Teknologi, 2019)
This study aims to determine the utilization of the worker’s time in the filling process, packaging department, a cup and bottled water company. Considering the aim of the study and the task characteristics, work sampling technique was used. Two production lines and two work stations were selected for time studyanalysis. In each work station, two workers with different tasks were involved for the time analysis. A number 586 and 1710 observations from Worker 1 in Line 1 and Line 2, and 586 and 1440 observations from Worker 2 in Line 1 and Line 2 were taken and observed. Results showed that the utilization of worker’s time are 31.7% and 33.6 % of Worker 1 in Line 1 and Line 2, and 25.6% and 21.0% of Worker 2 in Line 1 and Line 2. Results of significant testing showed that no significant differences were found for workers’ time utilization between Worker 1 in Line 1 and Worker 1 in Line 2 (Z=-0.82, p=0.41) and between Worker 2 in Line 1 and Worker 2 in Line 2 (Z=2.17, p=0.03) for α=0.01. Regarding findings in this study, it is reasonable for the management to consider work station which one worker per machine instead of two workers per one machine.